ATTITUDES OF GOVERNMENT SECONDARY SCHOOLS STUDENTS TOWARDS CO-SCHOLASTIC ACTIVITIES - Devi, Ayekpam Sheela; Singh, W. Jyotirmoy (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study aims to assess students’ attitudes toward co-scholastic activities in government secondary schools in Imphal West District, Manipur. A self-developed questionnaire was used to measure the attitudes of 100 students with a focus on testing the reliability of the instrument, determining overall attitudes, and comparing attitudes based on gender. The reliability of the questionnaire was satisfactory (Cronbach’s alpha = 0.784), and students exhibited positive attitudes toward co-scholastic activities. However, a significant gender difference was found, with male students showing more positive attitudes than female students. The study highlights the importance of gender-sensitive co-scholastic programs and provides valuable insights for educators to foster inclusive and equitable participation.